The Effects of Environmental Values on Gen Z’s E-Waste Recycling Intention - Ang, Yvonne S.M.; Mohammad, Noorita; Mohammad Shobri, Nor Diyana (Information Management and Business Review, 2023)
The rapid growth of electronic waste (e-waste) has become a pressing environmental concern, necessitating a deeper understanding of individuals’ intentions toward responsible e-waste management. This study aims to explore the relationship between e-waste recycling intentions using the Theory of Planned Behavior (TPB) while considering the influence of environmental values. The research design employs a quantitative approach, utilizing a survey questionnaire to collect data from 115 Gen Z respondents. The findings show that perceived behavioral control, subjective norms and environmental values influence the intention to recycle e-waste while attitude was not impactful in influencing e-waste recycling intention. The findings will offer valuable insights for policymakers, environmental organizations, and practitioners seeking to promote sustainable e-waste practices. Ultimately, the study aims to foster a more comprehensive understanding of how individual attitudes can be leveraged to drive positive changes in e-waste management and contribute to a more sustainable future.